Next Generation Welfare System and E-Government in Banjarbendo Village - Choiriyah, Ilmi Usrotin; Darmawan, Achmad Firnanda (Indonesian Journal of Public Policy Review, 2024)
Background: The effectiveness of social welfare information systems, especially the Next Generation Social Welfare Information System (SIKS-NG), is vital for local e-government initiatives. Specific Background: This study examines SIKS-NG's implementation in Banjarbendo Village, Sidoarjo, East Java, to evaluate its impact on service delivery. Knowledge Gap: Prior research highlights inconsistent effectiveness and issues related to resource adequacy and data accuracy in rural contexts. Aims: This research aims to assess SIKS-NG's effectiveness through qualitative analysis, focusing on indicators of goal achievement, integration, and adaptation. Results: The study finds that SIKS-NG operates effectively due to competent operators and sufficient infrastructure, though data inconsistencies pose challenges. Novelty: This research offers new insights into the successes and challenges of implementing SIKS-NG in a rural Indonesian setting. Implications: The findings emphasize the importance of ongoing training and infrastructure improvements to resolve data discrepancies, thereby enhancing the effectiveness of e-government in social welfare management. Highlights : Human Resource Competence: The effectiveness of SIKS-NG relies heavily on the training and skills of operators in information technology. Infrastructure Support: Adequate facilities, such as computers and internet access, are essential for smooth implementation. Data Accuracy Issues: Discrepancies between submitted and application data hinder overall program effectiveness. Keywords: SIKS-NG, e-government, social welfare, effectiveness, rural development